The function of derivational affixes found in highend magazine - Mahaputri, Anom Gayatri; Putra, I Gusti Bagus Wahyu Nugraha; Maharani, Putu Devi (Journal of Language and Applied Linguistics, 2021)
The objectives of this research are to know the function of derivational affixes and to analyze the word structure of derivational affixes found in HighEnd Magazine. This study focused on the function and the word structure of affixes attached in each word found in HighEnd Magazine. The magazine entitled HighEnd Magazine is used as the data source. In this research the writer used observation method in collecting the data and qualitative method was used to analyze the data. The data were analyzed by using theory from Katamba (1993) and Carstairs and McCarthy (2002). The researcher used formal and informal method to present the result of the analysis. There are 302 words attached by derivational affixes found in HighEnd Magazine. There are two functions of derivational morpheme they are class changing morpheme and class maintaining morpheme.